Sida rhomboidea. Roxb Leaf Extract Down-Regulates Expression of PPARγ2 and Leptin Genes in High Fat Diet Fed C57BL/6J Mice and Retards in Vitro 3T3L1 Pre-Adipocyte Differentiation - Thounaojam, Menaka C. (Molecular Diversity Preservation International (MDPI), 2011)
Sida rhomboidea. Roxb leaf extract (SRLE) is being used by the populace of North-East India to alleviate symptoms of diabetes and obesity. We have previously reported its hypolipidemic and anti-diabetic properties. In this study, we report the effect of SRLE on (i) in vivo modulation of genes controlling high fat diet (HFD) induced obesity and (ii) in vitro 3T3L1 pre-adipocyte differentiation and leptin release. Supplementation with SRLE significantly prevented HFD induced increment in bodyweight, plasma lipids and leptin, visceral adiposity and adipocyte hypertrophy. Also, SRLE supplementation reduced food intake, down regulated PPARγ2, SREBP1c, FAS and LEP expressions and up-regulated CPT-1 in epididymal adipose tissue compared to obese mice. In vitro adipogenesis of 3T3L1 pre-adipocytes was significantly retarded in the presence of SRLE extract. Also decreased triglyceride accumulation, leptin release and glyceraldehyde-3-Phosphate dehydrogenase activity along with higher glycerol release without significant alteration of viability of 3T3L1 pre-adipocytes, was recorded. Our findings suggest that prevention of HFD induced visceral adiposity is primarily by down regulation of PPARγ2 and leptin gene expression coupled with attenuation of food intake in C57BL/6J mice. SRLE induced prevention of pre-adipocytes differentiation, and leptin release further substantiated these findings and scientifically validates the potential application of SRLE as a therapeutic agent against obesity.